Enhancing Self-Assessment Using Social Learning Strategies And Learner Characteristic Factors In Massive Open Online Courses (MOOCS) For Language Learning - Abdullah, Mohd Mawardy; Mohamad, Siti Nurul Mahfuzah; Salam, Sazilah; Hashim, Hasmaini (Asian Research Publishing Network (ARPN), 2021)
Massive Open Online Courses (MOOCs) provides an effective learning platform with various high-quality educational materials accessible to learners from all over the world. On the other hand, assessment plays an important role to improve student performance in MOOC learning. However, issues in assessment designs contribute to a lack of student engagement. Hence, a suitable assessment design should be developed in MOOC for language learning. A literature review was performed to identify the key principles of social learning theory and dimensions of learner characteristics. Five research questions have been constructed to assist the study. Results of the study are then used in formulating a conceptual model for a Self-Assessment based on social learning strategies, and dimensions of learner characteristic factors. Findings of this study are two folds: i) a conceptual Self-Assessment model based on social learning strategies and learner characteristic factors for improving student engagement in MOOC for language learning, and ii) a Self-Assessment model based on social learning and learner characteristic factors to improve language learning using MOOC. In the future, student performance will be investigated using that Self-Assessment MOOC model in language learning based on social learning and learner characteristic factors.